The Nature And Dynamics Of Land-Related Communal Conflicts In Nigeria - Osegbue, Chike (COOU Journal of Multidisciplinary Studies, 2017)
Communal conflict has manifested itself as the most pandemic issue next to ethno-religious conflict in Nigeria with ownership, access to and use of land as the driver of the conflict. Communal conflict exists in all the geopolitical zones of the country though the character of the conflicts may differ between these zones. In Northern Nigeria for instance, while the character of the conflict revolves around farmers and herders, indigene-settler issues which occurs either in pure form and sometimes colored with ethnicity, in Southern Nigeria it is a combination of indigene-settler issues; farmer-Fulani herdsmen and political resource allocation. It is observed that most communal conflicts display clearly the paralysis of dialogue between political elites as well as the presence of fundamental socioeconomic and political grievances which divide societal groups. To this end the long term objective of this paper is to take the study of communal conflicts beyond the intractability and frequency of its occurrence to include in the main, an analysis of the underlying social, economic, and political causes of the crises. We adopted an ex-post facto research design, secondary source of data collection including a content analytical tool for analysis. The challenge of lack of effective conflict resolution mechanisms, horizontal inequalities, or inequalities among identity groups and feeling of marginalization by groups has intensified communal conflicts in Nigeria. The State needs to rethink its strategy and embrace conflict transformation strategy which focuses on the relationships between the parties in the midst of or previously engaged in a given conflict.